The Relationship between Coping Mechanisms and Anxiety Levels among Hypertensive Elderly in Rural Areas - Wahyuni, Adhitya Restu; Silvanasari, Irwina Angelia; Suswati, Wahyi Sholehah Erdah (Journal of Rural Community Nursing Practice, 2025)
Background: Hypertension is a prevalent condition among the elderly in rural areas. Anxiety in older adults with hypertension in these regions can significantly impact their blood pressure management, as it may hinder their adherence to medical treatment and healthy lifestyle practices. Purpose: This study aims to analyze the relationship between coping mechanisms and anxiety levels in elderly individuals with hypertension in rural areas. Methods: This quantitative study employs a cross-sectional approach. The population consisted of 198 elderly individuals, with a sample size of 132 elderly individuals with hypertension, selected using simple random sampling. The independent variable is the coping mechanism, and the dependent variable is the level of anxiety. Research instruments included the Coping Mechanism Questionnaire and the Hamilton Anxiety Rating Scale (HARS). Statistical analysis was conducted using the gamma test. Results: The findings indicate that the majority (59.1%) of participants utilized maladaptive coping mechanisms, while nearly half (41.7%) experienced severe anxiety. The gamma test revealed a P-value of 0.000 ≤ 0.05, with a contingency coefficient of -1.000, indicating a statistically significant and strongly negative relationship between coping mechanisms and anxiety levels in elderly individuals with hypertension. Conclusions: The study concludes that adaptive coping mechanisms are associated with lower anxiety levels in hypertensive elderly. Providing these individuals with information and counseling on effective coping mechanisms could help reduce anxiety and promote more adaptive coping strategies.